A new species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from South India, with keys to Indian members of the subgenus Gomphostilbia - Anbalagan, Sankarappan; Balachandran, Chellapandian; Prasanna, Vimalanathan Arun; Kannan, Mani; Dinakaran, Sundaram; Krishnan, Muthukalingan (Zootaxa, 2015)
A new black fly species, Simulium (Gomphostilbia) cauveryense sp. n., is described based on adult female, adult male, pupal and larval specimens collected from Kushalanagar, Karnataka, South India. This new species is placed in the decuplum subgroup of the batoense species-group within the subgenus Gomphostilbia. Keys to the species of the subgenus Gomphostilbia reported from India are provided for females, males, pupae and mature larvae.